2016
DOI: 10.1208/s12249-016-0512-4
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide Encrusted Multilayered Nano-Colloidal System of Andrographolide for Improved Hepatoprotection

Abstract: Andrographolide (AP), a phytoconstituent of Andrographis paniculata is reported as a potent hepatoprotective agent. However, utility of this molecule is restricted due to its low aqueous solubility, gastric instability and hence low bioavailability. It was aimed to formulate and characterize AP-loaded, natural biopolymer stabilized, multilayered nano-hydrocolloid delivery system. Nanoemulsion (NE) was formulated using layer-by-layer (LbL) technology via electrostatic deposition of chitosan over alginate encrus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The mean charge value on the particles prepared in our study was recorded as -24.43 ± 0.49 mV which is somewhat higher that recorded by Abbas et al, 2015, i.e., -17.2 ± 0.35 mV [22]. Similar results were recorded by Mishra et al [33] and Langella et al [35] with the zeta potential values of 22.9 to 31.01 mV.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The mean charge value on the particles prepared in our study was recorded as -24.43 ± 0.49 mV which is somewhat higher that recorded by Abbas et al, 2015, i.e., -17.2 ± 0.35 mV [22]. Similar results were recorded by Mishra et al [33] and Langella et al [35] with the zeta potential values of 22.9 to 31.01 mV.…”
Section: Discussionsupporting
confidence: 84%
“…The mean diameter of nanocapsules was recorded 160.57 ± 1.06 nm which was in accordance with [18] in which the mean diameter of nanocapsule was 159.85 ± 0.92 nm. Likewise, Mishra et al [33] prepared stable multilayered nanoemulsion using layer-by-layer technology, and particle size were in range of 90.8 to 167.8 nm. Many studies found that stability of encapsulated compound against oxidation was improved in multilayer nanoemulsions [34].…”
Section: Discussionmentioning
confidence: 99%
“…It is known as king of bitter due to the very bitter taste of all part of the plant and in Indonesia its name is sambiloto. In pharmacological research, it shows antidiabetic [1], cytotoxic effect [2], antimicrobial activity [3], anti-inflammatory [4], anti-hyperglycemia [5], antiatherosclerosis [6], antimalaria [7], hepatoprotective [8], and anticancer activity [9]; in vitro and in vivo studies.…”
Section: Introductionmentioning
confidence: 99%
“…Andrographolide (ADG) is one of the main active components isolated from the Chinese herb Andrographis paniculata . ADG has many pharmacological actions, including anti‐inflammatory, anti‐infection, anticancer, anti‐hyperglycemia, anti‐angiogenesis, hepato‐protection, antifertility, and anti‐HIV effects. However, its high lipophilicity (log P = 2.63), low aqueous solubility (74 μg mL −1 ), and poor stability seriously limit its application .…”
Section: Introductionmentioning
confidence: 99%